PENGARUH PENGGUNAAN E-MODUL BERBASIS COMPUTATIONAL THINKING TERHADAP PEMAHAMAN KONSEPTUAL SISWA SMK - Meyda; Jaka (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2026)
The~ low le~ve~l of conce~ptual unde~rstandi~ng among vocati~onal hi~gh school stude~nts i~n le~arni~ng i~s ofte~n cause~d by a le~arni~ng proce~ss that te~nds to focus on me~mori~zi~ng formulas rathe~r than logi~cal re~asoni~ng. The~ purpose~ of thi~s study i~s to analyze~ the~ e~ffe~ct of usi~ng Computati~onal Thi~nki~ng (CT)-base~d e~-modul on the~ conce~ptual unde~rstandi~ng of vocati~onal hi~gh school stude~nts. Thi~s study i~s a quanti~tati~ve~ study usi~ng a quasi~-e~xpe~ri~me~ntal me~thod. The~ de~si~gn e~mploye~d i~s a non-e~qui~vale~nt control group de~si~gn. The~ sample~ consi~ste~d of 80 te~nth-grade~ stude~nts at SMK Sukatani~ Purwakarta, di~vi~de~d i~nto an e~xpe~ri~me~ntal class and a control class. The~ re~sults of the~ study show a si~gni~fi~cant e~ffe~ct on stude~nts' conce~ptual unde~rstandi~ng, as e~vi~de~nce~d by the~ si~gni~fi~cance~ value~ of the~ I~nde~pe~nde~nt Sample~ T-Te~st of 0.001 (p < 0.05). The~ ave~rage~ N-Gai~n score~ i~n the~ e~xpe~ri~me~ntal class re~ache~d 0.72 (hi~gh cate~gory), whi~le~ the~ control class only score~d 0.28 (low cate~gory). The~ e~ffe~ct si~ze~ te~st usi~ng Cohe~n's d produce~d a value~ of 0.812, whi~ch falls i~nto the~ strong e~ffe~ct cate~gory. The~ re~sults i~ndi~cate~ that CT-base~d e~-module~s are~ e~ffe~cti~ve~ i~n e~nhanci~ng vocati~onal hi~gh school stude~nts’ abi~li~ty to gai~n a de~e~p unde~rstandi~ng of conce~pts through syste~mati~c thi~nki~ng.   Keywords: Computati~onal Thi~nki~ng; Conce~ptual Unde~rstandi~ng; E~-moduls; Vocati~on Hi~gh School Stude~nt.